2014
DOI: 10.1021/jf403896c
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of a Novel Glucan from Achatina fulica and Its Antioxidant Activity

Abstract: A novel glucan designated AFPS-IB was purified from Achatina fulica (China white jade snail) by anion-exchange and gel-permeation chromatography. Chemical composition analysis indicated AFPS-IB was composed of glucose, fucose, rhamnose, mannose, and galactose in a molar ratio of 189:2:1:1:2 and with an average molecular weight of 128 kDa. Its structural characteristics were investigated by Fourier transform infrared spectroscopy (FTIR), high performance liquid chromatography (HPLC), gas chromatography mass spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 32 publications
(63 reference statements)
1
20
0
Order By: Relevance
“…Snail flesh extract has the potential to treat asthma and tuberculosis (Padmanabhan and Sujana ). The glucan extract from China white jade snail ( Achatina fulica ) and hot water extract of Isada krill have significant antioxidant activities, suggesting their potentials as dietary antioxidant (Liao and others ; Koomyart and others ). Ziconotide, a peptide found in marine cone snail, is approved for analgesic use (Cheung and others ).…”
Section: Nutritive Value and Health Benefits Of Shellfishmentioning
confidence: 99%
“…Snail flesh extract has the potential to treat asthma and tuberculosis (Padmanabhan and Sujana ). The glucan extract from China white jade snail ( Achatina fulica ) and hot water extract of Isada krill have significant antioxidant activities, suggesting their potentials as dietary antioxidant (Liao and others ; Koomyart and others ). Ziconotide, a peptide found in marine cone snail, is approved for analgesic use (Cheung and others ).…”
Section: Nutritive Value and Health Benefits Of Shellfishmentioning
confidence: 99%
“…The NMR spectra of UP2 were shown in Fig 4 . According to previous studies [2, 4], the anomeric hydrogen chemical shifts of UP2 appear at δ 5.02, 4.95, 4.88 and 4.36 ppm. The heteronuclear single-quantum coherence (HSQC) spectrum of UP2 ( Fig 4C ), showed overlapping peaks around δ 4.88 ppm, indicating the presence of two different connections.…”
Section: Resultsmentioning
confidence: 54%
“…They are essential biological macromolecules, and are directly involved in life processes, exhibiting a variety of important biological functions [2, 7]. Furthemore, polysaccharides exhibit immune-enhancement, anti-tumor, antioxidant, and other biological activities [89].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical composition analysis showed that PV-P2 and PV-P3 had higher content of protein and uronic acid, which might explain their stronger antioxidant activities as compared to PV-P1. The most pronounced hypothesis is that free radicals can abstract hydrogen atoms at all ring C H bonds on carbohydrate [32]. Therefore, the stronger antioxidant activities of PV-P2 and PV-P3 may be attributed to their higher levels of active hydroxyl groups, suggesting that the chemical compositions and structures were critical for the antioxidant capacities of P. vulgaris polysaccharides.…”
Section: Oracmentioning
confidence: 99%